Հայկական մի առակի միջազգային զուգահեռները - Էդ. Մ. Ջրբաշյան (ՀՀ ԳԱԱ հրատ.)
Речь идет о басне «Князь и вдова», основанной на парадоксальной психологической ситуации: в ответ на гонения злого и жестокого князя вдова молится за продление его жизни, ибо боится, что преемник его будет еще злее. В Армении эта басня была записана в начале XIV века писателем-монахом Ованесом Ерзнкаци—Цорцореци (впервые издана Н. Я. Марром во втором томе его капитального труда «Сборники притч Вардана» в 1894 г.). This article is about the fable "The Prince and the Widow" based on the paradoxical- psychological situation: in answer to persecution of the wicked and cruel prince the widow is praying for the prolongation of his life since she is afraid that his successor will get more wicked. This fable was written in Armenia in early 14th century by Hovhannes Yerznkatsi-Tsortsoretsi, a writer and a priest (in the "Collections of the Parables of Vardan", second volume, 1894, first publisher N. Ya. Marr).
Keywords: Literature; Language and Literature; G Geography; Anthropology; Recreation; GR Folklore